Pengembangan Modul Informasi Objek Layanan Kesehatan pada Aplikasi Malang Sehat - Muh Wildan Shalahuddin; Herman Tolle; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Indonesian people have the right to obtain information about health, this is written in Undang-undang number 36 of 2009 chapter III article 7. Meanwhile, the government has an obligation to provide access to information, education, and health service facilities as stated in article 14 chapter 4 Undang-undang number 36 of 2009. However, based on the facts on the ground when interviews were conducted with several people in the city of Malang, it can be concluded that the current system is still conventional and requires improvements in the process of delivering information. The Malang city government innovates by applying the Smart City concept to solve this problem. The realization that was carried out was the development of an Android-based mobile application called Malang Sehat which was divided into 3 modules, namely the Health Data Collection and Monitoring module, the Health Services module and the last one that became the topic of this research was the Health Service Object Information module. This module was built using the Prototyping method with 5 process stages, namely communication, quick plan, quick design modeling, construction of prototype, and prototype delivery and feedback. The loop iteration will stop if the stakeholders state that the application has met the needs when providing feedback. After the iteration process is complete and the prototype has been declared to meet the needs, then the Functional, Usability, and Compatibility testing is carried out. On Functional testing produces a 100% success rate. Furthermore, the Usability test which was tested on 10 respondents resulted in a success rate of 98.57% and the final score of the System Usability Scale (SUS) reaching 84.75% with an adjective rating of